The Effect of Breastfeeding Practices of Undernourished Mothers in Rural Sierra Leone on Infant Growth and Mortality - Aminata Shamit Koroma; Kevin B. Stephenson; Per O. Iversen; Mark J. Manary; David Taylor Hendrixson (Children, 2024)
Breastfeeding provides optimal infant nutrition; however, <50% of infants are exclusively breastfed (EBF) for 6 months. We aimed to describe breastfeeding practices and their effects on growth and mortality among a high-risk mother-infant cohort in rural Sierra Leone. This was a secondary analysis of data from a randomized nutrition intervention trial among undernourished pregnant women. The study’s primary outcomes were infant weight and length gains at 6 weeks of age. We included 1270 singleton infants in the analysis, with 1092 (85.6%) having 24-week outcome data. At 6 weeks, 88% were EBF, but the rate of EBF decreased to 17% at 24 weeks. The EBF infants at 6 weeks had improved length (difference of 0.9 mm/week; 95% CI 0.4 to 1.3; p < 0.001) and weight (difference of 40 g/week; 95% CI 24 to 53; p < 0.001) gains compared to the non-EBF infants. At 12 weeks, the EBF infants had improved weight (difference of 12 g/week; 95% CI 2 to 22; p = 0.024) gain. The EBF infants had lower mortality than the infants who were not EBF (hazard ratio of 0.39; 95% CI 0.18 to 0.84; p = 0.017). In summary, the infants who were EBF had greater weight and length gain and reduced mortality than those who were not EBF. Efforts to improve breastfeeding should thus be prioritized to improve infant health.